2012
DOI: 10.1038/nbt.2141
|View full text |Cite
|
Sign up to set email alerts
|

Functional beta-cell maturation is marked by an increased glucose threshold and by expression of urocortin 3

Abstract: Insulin expressing cells that have been differentiated from human pluripotent stem cells in vitro lack the glucose responsiveness characteristic of mature β-cells. β-cell maturation in mice was studied to find genetic markers that enable screens for factors that induce bona fide β-cells in vitro. We find that functional β-cell maturation is marked by an increase in the glucose threshold for insulin secretion and by expression of the gene urocortin 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
370
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(408 citation statements)
references
References 14 publications
33
370
2
3
Order By: Relevance
“…Ucn3 is a late maturation marker for primary and stem cell-derived beta cells (Blum et al, 2012;van der Meulen et al, 2012) that continued to increase progressively weeks after beta cell expression of Nkx6-1 and Mafa reached steady state, and coincided with the gradual loss of Mafb from beta cells ( Figure 1A) (Artner et al, 2010).…”
Section: Ucn3-negative Immature Beta Cells Persist Throughout Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Ucn3 is a late maturation marker for primary and stem cell-derived beta cells (Blum et al, 2012;van der Meulen et al, 2012) that continued to increase progressively weeks after beta cell expression of Nkx6-1 and Mafa reached steady state, and coincided with the gradual loss of Mafb from beta cells ( Figure 1A) (Artner et al, 2010).…”
Section: Ucn3-negative Immature Beta Cells Persist Throughout Lifementioning
confidence: 99%
“…This is evident from the presence of a distinct population of immature beta cells at the islet periphery that does not yet express the late maturation marker Urocortin3 (Ucn3) (Blum et al, 2012;van der Meulen and Huising, 2014;van der Meulen et al, 2012). Similar Ucn3-negative beta cells are readily identifiable in human pancreas of different ages and in donors with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…By late gestation (around E18.5), the endocrine cells are loosely arranged as small clusters; at this stage bcells cannot sense glucose and secrete insulin [11,12]. Immediately after birth, b-cells undergo extensive proliferation and functional maturation [13,14]. Progenitor cells may linger in the postnatal pancreas, as suggested by lineage-tracing experiments that showed that a portion of duct cells labeled with sex-determining region box 9 (Sox9) [15] or carbonic anhydrase II could contribute to new endocrine cells [16].…”
Section: Onward Ngn3mentioning
confidence: 99%
“…Urocortin-3 expression has been used to identify mature, fully functional, β-cells during pancreas development 5 and is expressed at approximately equal levels in α-and β-cells in non-diabetic adult human pancreas 13 . Absence of detectable beta-cell urocortin-3 staining in all transplanted islets examined in the current study provides evidence for loss of end-differentiated phenotype despite maintained insulin expression and near-normoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to vascularised whole pancreas transplant where normalisation of β-cell secretory capacity has been confirmed 4 . During pancreas development co-expression of insulin and the peptide hormone urocortin-3 is a phenotypic marker of full β-cell maturation 5 . Maintenance of β-cell urocortin-3 expression is required for physiological regulation of insulin secretion, with urocortin-3 null mice having deficient insulin secretion during periods of high glucose 6 .…”
Section: Introductionmentioning
confidence: 99%